Appreciative Case Management: Using the Social Constructionism in Social Intervention - Ștefan Cojocaru (Expert Projects, 2021)
The article presents a research in the field of case management, experiencing two forms of it: problem-centered case and appreciative case management. For this, an experiment carried out on a six-month period, during which time we verified the results obtained by applying two different supervision models, problem-oriented supervision and appreciative supervision. Based on parallel process, the case management was changed. For this experiment ten cases were identified with various degrees of risk in child abandonment. When the appreciative case management was applied, the studied cases showed better results compared to the cases that were managed based on problem. In the case of services aimed at preventing child abandonment, it can be seen that the classical intervention focused on problem, lasting less than three months, has no positive effect on the clients’ situation. This practically means that in such circumstances, the financial, human and material resources used for an intervention that lasts less than three months are wasted without significant results. The appreciative case management produces tangible results after a shorter period of time by comparison to the classical intervention. This can be seen in the results obtained within the experiment, which are due to the use of the appreciative approach in intervention. Focusing on problems in social work and the attempt to solve them may sometimes not result in their resolution; the orientation towards identifying deficiencies and dysfunctionalities yields poorer results than the appreciative intervention and preserves the problem.